Effect of two prophylaxis methods on marginal gap of Cl V resin-modified glass-ionomer restorations - Soodabeh Kimyai; Fatemeh Pournaghi-Azar; Mehdi Daneshpooy; Mehdi Abed Kahnamoii; Farnaz Davoodi (Tabriz University of Medical Sciences, 2016)
Background. This study evaluated the effect of two prophylaxis techniques on the marginal gap of CI V resin-modified glass-ionomer restorations. Methods. Standard Cl V cavities were prepared on the buccal surfaces of 48 sound bovine mandibular incisors in this in vitro study. After restoration of the cavities with GC Fuji II LC resin-modified glass-ionomer, the samples were randomly assigned to 3 groups of 16. In group 1, the prophylactic procedures were carried out with rubber cup and pumice powder and in group 2 with air-powder polishing device (APD). In group 3 (control), the samples did not undergo any prophylactic procedures. Then the marginal gaps were measured. Two-way ANOVA was used to compare marginal gaps at the occlusal and gingival margins between the groups. Post hoc Tukey test was used for two-by-two comparisons. Statistical significance was set at P < 0.05. Results. There were significant differences in the means of marginal gaps in terms of prophylactic techniques (P < 0.001), with significantly larger marginal gaps in the APD group compared to the pumice and rubber cup group, which in turn exhibited significantly larger marginal gaps compared to the control group (P < 0.0005). In addition, the means of marginal gaps were significant in terms of the margin type (P < 0.001), with significantly larger gaps at gingival margins compared to the occlusal margins (P < 0.0005). Conclusion. The prophylactic techniques used in this study had a negative effect on the marginal gaps of Cl V resin-modified glass-ionomer restorations.